ANALISIS PENGUNGKAPAN CSR DAN ENVIRONMENTAL PERFORMANCE TERHADAP STOCK RETURN PADA PERUSAHAAN MANUFAKTUR - Michelle Anwar; Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research was conducted to explain the effect of disclosure of Corporate Social Responsibility and Environmental Performance on Stock Returns in consumer cyclical and consumer noncyclical manufacturing companies that have been listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample was selected using a purposive sampling method and there were 11 valid manufacturing companies to be tested in this study. Existing data were processed using multiple linear regression analysis with IBM SPSS (Statistical Product and Service Solution) software version 29 and Microsoft Excel 2013. The results of this study stated that Corporate Social Responsibility had no significant and positive effect on Stock Returns and Environmental Performance had no significant and negative effect on Stock Return. The implication of this research is the need to inform PROPER news through the right media and increase CSRD information that is attractive and transparent to generate positive signals for investors and increasing stock returns.